Enabling Customer Empowerment : Choice, Use, and Voice - Koning, Antonique (World Bank, Washington, DC, 2015)
The use of digital channels is changing the way financial services can be delivered to poor people. Growing mobile phone usage and the development of agent networks enable customer access too timely, low-cost digital financial services (DFS) (World Bank 2014). Despite this, active use of DFS is relatively low. In this brief, the author address the inactivity problem faced by many financial service providers (FSPs) and some of the underlying causes related to customers’ experiences. The author explores how empowering customers can help address this issue and the role FSPs can play. This exploratory Brief reflects our hypothesis that customer empowerment, here defined as a process that builds customer trust and confidence through an interactive relationship between providers and their customers, can lead to a win-win for both providers and customers.